Males tend to come earlier for eye care with the National Health Coverage Programme in private hospitals - Simanjuntak, Gilbert WS; Tan, Jannes F; Christine, Reinne Natali (Universa Medicina, 2018)
BackgroundCataract is the leading cause of blindness in Indonesia, and poverty is a major barrier to having cataract surgery. Increasing the proportion of adults that have regular, comprehensive eye examinations for cataract and other common eye health problems is one of the National Health Insurance (JKN) objectives. The objective of this study was to determine the impact of vision insurance on eye care utilization of cataract patients in private hospitals with the JKN system as social intervention. MethodsA cross-sectional study was conducted involving 230 cataract patients in a private hospital. Inclusion criteria were patients with cataract surgery, diagnosis and follow up visit minimally two months after surgery. A multiple logistic regression was used to analyse the data.ResultsInitial visual acuity (VA) was 0.13 Â± 0.15 and final VA was 0.91 Â± 0.15. Two patients had final VA of 0.2 and 0.15, respectively, in which the first was associated with persistent corneal edema and diabetes mellitus, and the other with corneal scar. Age, gender, and level of education were not associated with VA at the first visit (p>0.05). Further analysis using a multiple logistic regression model was found to be significant (p=0.0104), with gender being associated with preoperative vision, where males tend to come earlier to undergo cataract surgery/treatment.ConclusionMales tend to come earlier than females for cataract surgery with the National Health Insurance (JKN) programme, despite the social intervention of the programme.